Measurement of residence time distribution of liquid phase in an industrial-scale continuous pulp digester using radiotracer technique. (May 2016) - Sheoran, Meenakshi; Goswami, Sunil; Pant, Harish J.; Biswal, Jayashree; Sharma, Vijay K.; Chandra, Avinash; Bhunia, Haripada; Bajpai, Pramod K.; Rao, S. Madhukar; Dash, A.
Abstract: A series of radiotracer experiments was carried out to measure residence time distribution (RTD) of liquid phase (alkali) in an industrial-scale continuous pulp digester in a paper industry in India. Bromine-82 as ammonium bromide was used as a radiotracer. Experiments were carried out at different biomass and white liquor flow rates. The measured RTD data were treated and mean residence times in individual digester tubes as well in the whole digester were determined. The RTD was also analyzed to identify flow abnormalities and investigate flow dynamics of the liquid phase in the pulp digester. Flow channeling was observed in the first section (tube 1) of the digester. Both axial dispersion and tanks-in-series with backmixing models preceded with a plug flow component were used to simulate the measured RTD and quantify the degree of axial mixing. Based on the study, optimum conditions for operating the digester were proposed. Highlights: Radiotracer experiments were conducted to measure RTD of liquid phase in a pulp digester Mean residence times of white liquor were measured Axial dispersion and tanks-in-series models were used to investigate flow patterns Parallel flow paths were observed in first section of the digester Optimized flow rates of biomass and liquor were obtained